Metagenomic Next-Generation Sequencing for Diagnostically Challenging Mucormycosis in Patients with Hematological Malignancies - Zhang M; Lu W; Xie D; Wang J; Xiao X; Pu Y; Meng J; Lyu H; Zhao M (Infection and Drug Resistance, 2022)
Meng Zhang,1,* Wenyi Lu,2,* Danni Xie,1 Jiaxi Wang,1 Xia Xiao,2 Yedi Pu,2 Juanxia Meng,2 Hairong Lyu,2 Mingfeng Zhao2 1First Center Clinic College of Tianjin Medical University, Tianjin, 300192, People’s Republic of China; 2Department of Hematology, Tianjin First Central Hospital, Tianjin, 300192, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mingfeng Zhao; Hairong Lyu, Department of Hematology, Tianjin First Central Hospital, Tianjin, 300192, People’s Republic of China, Email mingfengzhao@sina.com; 18802235939@163.comBackground: Metagenomic next-generation sequencing (mNGS) is a fast, sensitive and accurate diagnostic method for pathogens detection. However, reports on the application of mNGS in mucormycosis remain scarce.Methods: From January 2019 to December 2021, we recruited 13 patients with hematological malignancies who were suspected of mucormycosis and completed mNGS in D20. Then we retrospectively analyze the clinical data, diagnosis, therapeutic process, and outcomes. In order to evaluate the diagnostic value of mNGS in hematological malignancies patients with suspected mucormycosis.Results: All patients had high risk factors of Invasive Fungal Disease, including hematopoietic stem cell transplantation, immunosuppression, glucocorticoids, etc. The clinical presentations were pulmonary (n=9), rhino-orbito-cerebral (n=4). But the manifestations were nonspecific. All enrolled patients completed mNGS. And most (8/13, 61.54%) of the samples were from blood. Fungi can be detected in all specimens, including Rhizopus (n=7), Rhizomucor (n=4) and Mucor (n=2). In addition, 7/13 (53.85%) specimens were detected bacteria at the same time and virus were detected in 5/13 (38.46%). Histopathological examination was completed in 5 patients, 3 of which were completely consistent with the results of mNGS. After treatment, 6 patients were cured, while the other 7 patients died.Conclusion: mNGS may be a complementary method for early diagnosis, especially for patients who are not suitable for histopathology examination or unable to obtain culture specimen. mNGS can also help detect bacteria and viruses simultaneously, allowing for appropriate and timely antibiotic administration and thus improving patient outcomes.Keywords: metagenomic next-generation sequencing, mucormycosis, retrospectively, hematological malignancies, invasive fungal disease